Enchanted Ground: The Spirit Room of Jonathan Koons by Sharon Hatfield - Ruffles, Tom (Journal of Scientific Exploration, 2020)
The mediumship of Jonathan Koons is much less well-known than that of the Fox sisters, though during the 1850s his Spirit Room at Athens, Ohio, became a desirable destination for Spiritualists keen to seek contact with the spirit world. There they experienced a wide variety of phenomena that would shortly become staples of the movement. Local resident and nonfiction author Sharon Hatfield has made a painstaking examination of Koons’s life and career based on the available evidence, setting it in the context of the developing religion of Spiritualism. Koons was born in Pennsylvania in 1811. He moved to Mount Nebo–actually a large hill in Athens County, southeastern Ohio, in the foothills of the Appalachians–in 1835, where he farmed and became patriarch to a sizeable family. In his youth he had had a mystical experience involving a ‘visit to the realm of light’ which led him to believe he had met an angel. Originally Presbyterian, he abandoned the religion as he found its Calvinism uncongenial, becoming as he put it an ‘infidel’. He lacked a formal education but read widely. In early 1852 he encountered reports of the Fox sisters’ mediumship and decided to investigate the subject. He attended séances and, initially skeptical, was told he himself had a gift. Trying it, he found a new religious faith. He also discovered that other members of his family, particularly his eldest son Nahum, had mediumistic abilities. After a while, they were told by Spirit to build a dedicated room to hold about 20-25 people, indicating that séances were to include more than his immediate friends and family. Koons duly built a log cabin on the farm to the given specifications and furnished it, including with musical instruments, as instructed. The stage was then set for public séances.